Averting Expenditures and Willingness to Pay for Electricity Supply Reliability - Niroomand, Naghmeh; Jenkins, Glenn P. (Cambridge Univ Press, 2020)
Nepal has suffered from the worst electricity shortages in South Asia. This study is an attempt to measure the willingness to pay for an improved service using a model of revealed preference. Respondents are asked about the actions they are taking to reduce the impact on their household or business of scheduled and unscheduled outages and more stable voltage. We estimate the averting expenditures that were being incurred to compensate for the lack of reliability of the electricity service. The estimated cost of the averting actions as a percentage of the electricity bills is 53 % for households, 47 % for small businesses, 46 % for medium businesses, and 35 % for large businesses. Based on the estimations, we find that in 2017 the annual benefit from improving the reliability of the electricity service would be approximately US$ 188 million with a present value over 20 years of US$ 1.6 billion.
Keywords: averting expenditures; electricity; reliability; revealed preference; willingness to pay